Reaction of soybean cultivars to Meloidogyne incognita race 3 - Teixeira, Renato Andrade; Barbosa, Kássia Aparecida Garcia; Rocha, Mara Rúbia da (Científica, 2017)
Soybean crops are attacked by several pathogens. Among these, there are nematodes of the Meloidogyne genus, which are responsible for yield reduction. Among several control methods against these pathogens, one consists of using resistant cultivars. The objective of this study was to evaluate the reaction of 27 soybean cultivars to the nematode Meloidogyne incognita race 3. Two experiments were conducted under greenhouse conditions, in a completely randomized design, with 27 treatments and six replications. Plants were kept in plastic cups with capacity for 400 mL of sterilized substrate (soil + sand) and were artificially inoculated with a suspension of 2000 eggs and J2 of M. incognita race 3/plant. Evaluations were performed sixty days after inoculation (DAI), in order to determine nematode population density in the roots and reproduction factor (RF). Through experiment results, four soybean cultivars were selected, of which three were resistant (BRSGO Paraíso, NA 7255 RR and NS 7490 RR) and one was susceptible (BRSGO Santa Cruz). The cultivars aforementioned were inoculated with four different M. incognita Race 3 inoculum concentrations. Thus, an experiment was conducted in a completely randomized design, in a 4 x 4 factorial, with 12 replications. Evaluations were performed at 10 DAI, when the number of J2 and J3/root system was observed. At 45 DAI, nematode population density in the roots was evaluated. NS 7476, NS 7490 RR, NA 8015 RR, NA 7620 RR, BRSGO Graciosa, P98Y70, CD 237 RR, P98Y51 and UFU Milionária cultivars showed resistant behavior, as they were similar to the resistance standards used. NA 7255 RR and NS7490 RR cultivars behaved as M. incognita race 3-resistant with the use of the inoculum concentration of 4000 eggs/plant, which seems to be the ideal concentration to evaluate the reaction of cultivars to this nematode. Evaluations of M. incognita race 3 penetration in the roots were not a good parameter to evaluate cultivar behavior.